CFD Analysis of Flow Over Backward Facing Step at Different Inclination Angle - Sanjeev Kumar Gupta, Nitin Kukreja (International Journal of Advanced Science and Technology, 2020)
CFD analysis of single backward facing step is done in this paper. The impact of step point and extension proportion on partition length is contemplated and contrasted and test results revealed in writing [1]. The progression edges considered are 150, 300, 450, and 900, while the development proportions considered are 1.5 and 2.0. The geometrical modeling is carried out in ICEM and the numerical simulation & post processing was carried out in commercial CFD code- ANSYS Fluent 15. A two-dimensional isolated renormalized gathering k-Ԑ model is utilized for doing reattachment. The examination of the outcomes indicated that with the increment in step edge and extension proportion, the reattachment length (Lr) increments. Impact of Reynolds number (Re) is likewise examined by shifting it between 15500 to 64500 and it additionally indicated that Lr increments with an expansion of the Re.